Surgical Management of Bilateral Venous Malformation (Cavernous Hemangiomas) of the Maxillary Sinus. (10th February 2020) - Anzai, Takashi; Ito, Shin; Yamashita, Atsushi; Ide, Takuma; Tajima, Shori; Okada, Hiroko; Matsumoto, Fumihiko; Ikeda, Katsuhisa
Abstract : According to International Society for the Study of Vascular Anomalies classification 2018, "hemangioma" should be classified as either vascular tumor or vascular malformation (VM). So-called "cavernous hemangioma" is categorized as VM. VM rarely involves the mucous membranes of the sinonasal cavity and typically arises unilaterally from the sinonasal cavity. Bilateral VM of the maxillary sinus is extremely rare. To the best of our knowledge, there is no previous report of bilateral VM of the maxillary sinus. Here, we describe the surgical treatment of bilateral cavernous hemangiomas of the maxillary sinus. These tumors were successfully resected by endoscopic modified medial maxillectomy (EMMM) after embolization. Endoscopic sinus surgery, particularly EMMM, produces access to the bilateral maxillary sinus and can prevent several complications.